2020
DOI: 10.25304/rlt.v28.2339
|View full text |Cite
|
Sign up to set email alerts
|

Peer-graded individualised student homework in a single-instructor undergraduate engineering course

Abstract: This article reports on the implementation of a programme of individualised, peer-graded homework assignments in a large-scale engineering course, with minimal resources. Participation in the programme allows students to receive grades for problem-solving work in a setting more conducive to learning than the traditional final examination. The homework programme was designed to support the ordinary course work and examination preparation of students along the semester, rather than an expansion of the curriculum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…The anonymity offered by online evaluation collectors enhances the reliability of the feedback provided by participants [69]. With the increasing adoption of self-reported evaluation and immediate feedback from actual participants in TBL contexts, coupled with attributes of the group learning process from the previous phase, all this evaluation and feedback data can be synchronized with the student model and subsequently used for various algorithmic grouping purposes within LA [70].…”
Section: Discussionmentioning
confidence: 99%
“…The anonymity offered by online evaluation collectors enhances the reliability of the feedback provided by participants [69]. With the increasing adoption of self-reported evaluation and immediate feedback from actual participants in TBL contexts, coupled with attributes of the group learning process from the previous phase, all this evaluation and feedback data can be synchronized with the student model and subsequently used for various algorithmic grouping purposes within LA [70].…”
Section: Discussionmentioning
confidence: 99%
“…Results revealed that both experimental groups who used paper-based or online homework were more successful than the control group that not used any kind of homework. Results of Cleynena et al (2020) who studied the effects of a homework program on engineering students and discovered positive effects of homework are also supported by Yavich and Davidovitch (2020), but Yavich and Davidovitch (2020) also signify the long term benefits of homework such as teaching time-management and increasing problem-solving abilities. Karatabak et al (2020), who researched the distance education with and without homework, found that homework creates positive differences in distance education.…”
Section: Introductionmentioning
confidence: 88%
“…Nowadays, digital systems facilitate in-class peer evaluation activities promptly and anonymously (Cleynen et al, 2020). This provides teachers with greater flexibility in integrating peer evaluation into their class design.…”
Section: Peer Evaluation In Team-based Learning (Tbl)mentioning
confidence: 99%
“…Peer evaluation systems offer learners a scaffold to evaluate their group members and receive real-time feedback with reduced bias, enhanced individualism and privacy protection (Cleynen et al, 2020;Ismail et al, 2019). In online evaluation systems, both the evaluation outputs and the evaluation processes of raters can be traced, providing valuable data for learning analytics applications as part of the learner model attribute.…”
Section: Data-driven Peer Evaluation With Learner Modelmentioning
confidence: 99%